Gamma Glutamyltransferase Reduction Is Associated With Favorable Outcomes in Pediatric Primary Sclerosing Cholangitis. Issue 11 (25th September 2018) - Deneau, Mark R.; Mack, Cara; Abdou, Reham; Amin, Mansi; Amir, Achiya; Auth, Marcus; Bazerbachi, Fateh; Marie Broderick, Anne; Chan, Albert; DiGuglielmo, Matthew; El‐Matary, Wael; El‐Youssef, Mounif; et al.
Abstract : Adverse clinical events in primary sclerosing cholangitis (PSC) happen too slowly to capture during clinical trials. Surrogate endpoints are needed, but no such validated endpoints exist for children with PSC. We evaluated the association between gamma glutamyltransferase (GGT) reduction and long‐term outcomes in pediatric PSC patients. We evaluated GGT normalization (< 50 IU/L) at 1 year among a multicenter cohort of children with PSC who did or did not receive treatment with ursodeoxycholic acid (UDCA). We compared rates of event‐free survival (no portal hypertensive or biliary complications, cholangiocarcinoma, liver transplantation, or liver‐related death) at 5 years. Of the 287 children, mean age of 11.4 years old, UDCA was used in 81% at a mean dose of 17 mg/kg/day. Treated and untreated groups had similar GGT at diagnosis (314 versus 300, P = not significant [NS]). The mean GGT was reduced at 1 year in both groups, with lower values seen in treated (versus untreated) patients (99 versus 175, P = 0.002), but 5‐year event‐free survival was similar (74% versus 77%, P = NS). In patients with GGT normalization (versus no normalization) by 1 year, regardless of UDCA treatment status, 5‐year event‐free survival was better (91% versus 67%, P < 0.001). Similarly, larger reduction in GGT over 1 year (> 75% versus < 25% reduction) was also associated with improved outcome (5‐year event‐free survival 88% versus 61%, P = 0.005). Conclusion: A GGT < 50 and/or GGT reduction of > 75% by 1 year after PSC diagnosis predicts favorable 5‐year outcomes in children. GGT has promise as a potential surrogate endpoint in future clinical trials for pediatric PSC. Abstract : We evaluated the association between normalization of gamma glutamyltransferase(GGT) and long‐term liver outcomes in pediatric primary sclerosing cholangitis (PSC). Patients who have a normalized GGT at one year after diagnosis of PSC have a much more favorable outcome compared to those with persistently abnormal GGT. GGT is a useful biomarker in pediatric PSC.